Digital Entrepreneurship: Toward a Digital Technology Perspective of Entrepreneurship - Nambisan, Satish (Entrepreneurship Theory and Practice, 2017)
New digital technologies have transformed the nature of uncertainty inherent in entrepreneurial processes and outcomes as well as the ways of dealing with such uncertainty. This has raised important questions at the intersection of digital technologies and entrepreneurship—on digital entrepreneurship. We consider two broad implications—less bounded entrepreneurial processes and outcomes and less predefined locus of entrepreneurial agency—and advance a research agenda that calls for the explicit theorizing of concepts related to digital technologies. In articulating the promise and value of such a digital technology perspective, we consider how it would build on and enrich existing entrepreneurship theories.